Design and development of a food tray table for commercial aircraft using hybrid composites - Mohd Nor, Ariff Farhan; Hameed Sultan, Mohamed Thariq; Ariffin, Ahmad Hamdan (Centre for Advanced Research on Energy, Faculty of Mechanical Engineering, Universiti Teknikal Malaysia Melaka, 2017)
This research attempted to propose a newly-developed material, which has natural fiber in hybrid composites with less sustainability issues. Kenaf (K) and jute (J) are employed to hybrid with fiberglass (FB). This research aims to analyze the damage characteristic from flexural and impact testing at different layer configuration. Hybrid composites with four different configurations SP1 (FG-K-J-K-FG), SP2 (FG-K-K-K-FG), SP3 (FG-J-J-J-FG) and SP4 (FG-J-K-J-FG) are fabricated in the first stage for flexural testing. In the second stage, two best configurations are subjected to low-velocity impact at energy levels range 10J to 40J. The results show that SP3 and SP4 configurations possess 90% better mechanical properties while SP3 shows the best configuration for impact test.